Pengaruh Range Of Motion (Rom) Aktif Terhadap Peningkatan Kekuatan Otot Pada Lansia Dengan Reumathoid Arthritis Di Panti Sosial Lanjut Usia Mandalika NTB - Nurhayati Nurhayati; Nia Firdianti Dwi Admojo; Rahmani Ramli; I Gusti Ayu Mirah Adhi; Nurul Ilmi; Ageng Abdi Putra; Ni Wayan Udayani; Endah Sulistiyani (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: As the aging process occurs, the elderly are very vulnerable to experiencing health problems because their body parts decline. One of the disorders that often occurs in the elderly is degenerative disease, one of which is rheumatoid arthritis. Rheumatoid arthritis is an inflammatory disorder that primarily affects the synophal membrane of the joints and is generally characterized by pain, stiffness and fatigue in the joints and muscles. Range of motion (ROM) exercises can reduce stiffness, increase and maintain joint mobility and increase muscle joint flexibility. Purpose: the aim of this research is to determine the effect of range of motion on increasing muscle strength in elderly people with rheumatoid arthritis. Method: This research method is a quantitative research with a pre-experimental design using the One Group Pretest-Posttest Design method. Results: The results of the univariate analysis are that there are 16 elderly people with an average age of 70-79 years, namely 10 elderly people (62.8%) and dominated by women, namely 10 elderly people ( 62.8%). Meanwhile, the results of the bivariate analysis showed that the muscle strength level of the right leg was p=0.02 and the left leg was p=0.04. The conclusion of this study is that there is an influence of range of motion on the level of muscle strength in elderly people with rheumatoid arthritis in the Mandalika NTB elderly social institution.